Electric Field Mill, an Effective Methodology to Measure the Localized Lower Atmospheric Electric Field. (2020) - Agarwal, Anupma; Bhattacharya, S.; Chaudhari, Suryanshu
Abstract: Atmospheric electric field is an utmost parameter to study the dynamics of earth's atmosphere. Response of electric field may give the idea of localized atmospheric agitations. Electric field mill monitoring system monitors the atmospheric electric field variations which help to investigate and characterize the atmospheric variability in dissimilar weather conditions including thunderstorm, rainfall, lightning and alarming condition of seismic activities. Different patterns of atmospheric electric field pertains the various climatic conditions. The objective of EFM is to provide the nearly continuous survey of atmospheric electric field which may arise due to the coupling of atmospheric perturbations in lower earth atmosphere hence causing the changes in the complexities of the localized atmospheric electric field